The Effectiveness of Lifestyle-Focused Cognitive Behavioral Therapy versus Semantic Cognitive Restructuring Therapy on Chronic Fatigue in Patients with Irritable Bowel Syndrome - M Akbari Ebtekar; SO Emadian; B Mirzaian (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Gastrointestinal diseases are one of the most important and common chronic non-communicable diseases that impose a great economic burden and psychological pressure on society and the healthcare system. Considering the ambiguity in the field of cognitive etiology and treatment of irritable bowel syndrome, this study was conducted to compare the effectiveness of lifestyle-focused cognitive behavioral therapy versus semantic cognitive restructuring therapy on chronic fatigue in patients with irritable bowel syndrome. Methods: This cross-sectional study was conducted among 45 patients with irritable bowel syndrome who referred to a private clinic. Patients were assigned into 3 groups (n=15) of lifestyle-focused cognitive behavioral therapy, semantic cognitive restructuring therapy, and a control group that did not receive any cognitive therapy with a pretest-posttest design. The Multidimensional Fatigue Inventory with 5 subscales of general fatigue, physical fatigue, reduced activity, reduced motivation, and mental fatigue was used for data collection. The total score of the patient's fatigue intensity is obtained from 0 to 100, where a score of 20-40 indicates low fatigue, 40-60 indicates moderate fatigue, and a score above 60 indicates high fatigue in the individual. Groups were compared before, after and one month after treatment. Findings: 22 women (48.9%) and 23 men (51.1%) in the age group of 25-49 years participated in this study. The findings showed that lifestyle-focused cognitive behavioral therapy with a score of (53.53±11.12) and semantic cognitive restructuring therapy with a score of (60.40±14.57) in the post-test, and with scores (55.80±11.68 and 59.72±14.94, respectively) in the follow-up after four months were effective on chronic fatigue in patients with irritable bowel syndrome (p<0.05). These two intervention groups also showed a significant difference compared with the control group (64.53±15.70 and 64.46±15.77, respectively) (p<0.05). Conclusion: The results of the study showed that lifestyle-focused cognitive behavioral therapy and semantic cognitive restructuring therapy are effective on chronic fatigue in patients with irritable bowel syndrome.